Investigating non‐ignorable dropout in panel studies of residential mobility. Issue 2 (20th September 2013) - Washbrook, Elizabeth; Clarke, Paul S.; Steele, Fiona
Summary We consider the effect of non‐ignorable dropout in the analysis of residential mobility in household panel surveys. To investigate the effect of such dropout, we consider two types of selection model: the first allows dropout to depend directly on the individual's potentially missing moving status, and the second is a Heckman‐type selection model with correlated errors. We discuss the identification and estimation of these models and use simulations to study the role of exclusion restrictions in minimizing the dependence of inferences on unverifiable parametric assumptions. The models are both applied to data from the British Household Panel Survey.